Effects of underwater noise on marine mammals - Erbe, Christine (Springer New York LLC, 2012)
Public concern about the effects of underwater noise on marine mammals has steadily increased over the past few decades. Research programs have been developed around the globe to investigate noise impacts. Government departments in many countries regulate underwater noise emission. Industries, in particular the oil and gas industry, undertake environmental impact assessments of underwater noise expected from planned marine activities and submit these to regulatory agencies as part of a permit application process. Lawsuits have been brought against the Navy in an attempt to protect marine mammals from sonar testing. The number and diversity of stakeholders in the management of noise and marine animals is great. Marine Mammals and Noise (Richardson et al. 1995) was the first book to review and synthesize research on the noise effects on marine mammals. In the 15 years since then, a handful of review projects have been undertaken, with focus on specific aspects (e.g., Committee on Characterizing Biologically Significant Marine Mammal Behavior 2005; Committee on Potential Impacts of Ambient Noise in the Ocean on Marine Mammals 2003; National Research Council 2000; Nowacek et al. 2007; Southall et al. 2007).